2004
DOI: 10.1055/s-2004-817848
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Plasma Membrane Ca2+‐ATPase in the Short‐Term Response of Arabidopsis thaliana Cultured Cells to Oligogalacturonides

Abstract: Treatment of Arabidopsis thaliana cells with oligogalacturonides (OG) initiates a transient production of reactive oxygen species (ROS), the concentration of which in the medium peaks after about 20 min of treatment. The analysis of OG effects on Ca (2+) fluxes shows that OG influence both Ca (2+) influx and Ca (2+) efflux (measured as (45)Ca (2+) fluxes) in a complex way. During the first 10 - 15 min, OG stimulate Ca (2+) influx and decrease its efflux, while at successive times of treatment, OG cause an incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 48 publications
1
28
0
Order By: Relevance
“…A change of free calcium concentration might alter the loosely bound calcium in the cell wall and intercellular space, together with the evidence of high total calcium content found in the oil sunflower leaves might be loosely bound calcium and free calcium, indicating that the entering calcium was partially stored in vacuole or bound to pectins in the middle lamella and maintains the cell wall stability and integrity (Hanson 1984;Palta 1996;Hirschi 2004). concentration in cytosol; this notion was in agreement with the result of our cytosolic Ca 2 ' fluorescence intensity and the findings from other groups (Beffagna et al 2000;Sanders et al 2002;Romani et al 2004).…”
Section: Discussionsupporting
confidence: 93%
“…A change of free calcium concentration might alter the loosely bound calcium in the cell wall and intercellular space, together with the evidence of high total calcium content found in the oil sunflower leaves might be loosely bound calcium and free calcium, indicating that the entering calcium was partially stored in vacuole or bound to pectins in the middle lamella and maintains the cell wall stability and integrity (Hanson 1984;Palta 1996;Hirschi 2004). concentration in cytosol; this notion was in agreement with the result of our cytosolic Ca 2 ' fluorescence intensity and the findings from other groups (Beffagna et al 2000;Sanders et al 2002;Romani et al 2004).…”
Section: Discussionsupporting
confidence: 93%
“…Ca 2+ homeostasis is also controlled through the function of Ca 2+ ATPases, and our data show that FLS2 forms a complex with ACA8. It is possible that FLS2 transphosphorylates the Ca 2+ ATPase to regulate its activity, as ACA10 is differentially phosphorylated upon flg22 treatment (Benschop et al, 2007 (Romani et al, 2004). In line with this assumption, Ca 2+ fluxes triggered by the MAMP cryptogein in N. benthamiana were increased in amplitude and duration when endoplasmic reticulum-localized NbCA1 was silenced (Zhu et al, 2010).…”
Section: Discussionmentioning
confidence: 76%
“…Likewise, chemical inhibition of Ca 2+ ATPase function resulted in reduced ROS production in response to the fungal MAMP oligogalacturonide, placing ACA proteins upstream of RbohD (Romani et al, 2004). As Rboh proteins contain two EF hand motifs in their N-terminal domains (Ogasawara et al, 2008), an altered Ca 2+ signature in aca8 aca10 plants may impair ROS generation catalyzed by the NADPH oxidases.…”
Section: +mentioning
confidence: 99%
“…5, A and B). Stimulation of the active EY-sensitive Ca 2+ efflux across the PM by ROS was reported in a single study on an Arabidopsis cell culture (Romani et al, 2004). It was shown that ROS generated by oligogalacturonide treatment assisted Ca 2+ -ATPase activation by calmodulin.…”
Section: Pas and Ohmentioning
confidence: 88%
“…1A). Eosine yellow (EY; 0.5 mM), a specific inhibitor of the PM Ca 2+ pump (Romani et al, 2004;Beffagna et al, 2005) and is sensitive to EY (Fig. 1B), suggesting the Ca 2+ -ATPase as a possible candidate (White and Broadley, 2003).…”
mentioning
confidence: 99%